Communicating CSR in the digital age: an exploratory study of a CSR award winning company in Malaysia - Ahmad, Zeti Azreen (Journal of Education and Social Science (JESOC), 2016)
The role of the government in driving corporate social responsibility (CSR) practices in Malaysia remains fundamental from the start. Unlike its Western counterparts such as the United States or United Kingdom, Malaysian government has set in motion special CSR funding and incentives; which include tax exemptions for companies that have made substantial social investment to society. CSR has been embedded in business practices to attract international investors and to secure major business contracts. Ahmad (2012) found that CSR practice in Malaysia primarily functioned as a business strategy to remain competitive and subsequently drive the nation’s economic growth. CSR communication has received increased attention particularly after Bursa Malaysia made it mandatory for public listed firms to report on their CSR activities. However, conventional CSR reporting; either included in corporate annual report or standalone CSR report merely served to inform organizations’ commitment in pursuing responsible business practices without making any serious attempt to establish a direct and constant engagement with CSR’s key stakeholders i.e. CSR recipients, employees, community, volunteers and investors. This study argues that continues engagement with organizations’ stakeholders is essential to secure a continuous trust and support towards CSR initiatives. Social media could fill this void as they provide a strategic avenue for companies to have a timely and direct engagement with diverse stakeholders. At present, there is no empirical evidence found on the usage of social media to communicate organizations’ CSR initiatives among Malaysian firms. At the same time, to what extent CSR communication using the social media has helped organizations to engage with stakeholders, has not been sufficiently explored. In view of this gap, the study has addressed the overarching question on how organizations in Malaysia used social media to communicate CSR with their stakeholders. The findings among others showed a strong tendency to adopt a one-way communication strategy in communicating CSR related information with stakeholders. Despite social medias’ distinctive feature in fostering two-way communications, CSR communication remained as non-interactive. This research offers a critical insight on how CSR communication strategy has evolved in this digital era, and thus this would be an original contribution to the literature, particularly in the area of CSR communication in Malaysia.